Rat astrocytes are more supportive for mouse OPC self‐renewal than mouse astrocytes in culture. Issue 8 (23rd March 2017) - Cheng, Xuejun; Xie, Binghua; Qi, Jiajun; Zhao, Xiaofeng; Zhang, Zunyi; Qiu, Mengsheng; Yang, Junlin
ABSTRACT: Mouse primary oligodendrocyte precursor cells (OPCs) are increasingly used to study the molecular mechanisms underlying the phenotype changes in oligodendrocyte differentiation and axonal myelination observed in transgenic or mutant mouse models. However, mouse OPCs are much more difficult to be isolated by the simple dissociation culture of brain tissues than their rat counterparts. To date, the mechanisms underlying the species difference in OPC preparation remain obscure. In this study, we showed that astrocytes from rats have a stronger effect than those from mouse in promoting OPC proliferation and survival in vitro . Mouse astrocytes displayed significantly weaker viability in culture and reduced potential in maintaining OPC self‐renewal, as confirmed by culturing OPCs with conditioned media from rat or mouse astrocytes. These results explained the reason for why stratified cultures of OPCs and astrocytes are difficult to be achieved in mouse CNS tissues. Based on these findings, we adopted inactivated rat astrocytes as feeder cells to support the self‐renewal of mouse cortical OPCs and preparation of high‐purity mouse OPCs. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 907–916, 2017